Efficient Distributed Consensus Algorithm in BIoT Environment - Young-Bok Cho, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, the importance of telemedicine is emerging in the era of Untect. In this paper, the proposed algorithm guarantees its transparency and reliability based on a blockchain-based lightweight distributed consensus algorithm that supports accurate diagnosis and reading by consensus of distributed image-reading experts in a telemedicine environment. However, since the blockchain consensus algorithm requires high-specification computing power or generates network traffic, its use in relatively low-performance Internet-of-Things (IoT) devices is very limited. Therefore, in this paper, we proposed a distributed consensus algorithm for reading medical images based on a blockchain suitable for IoT telemedicine environments and showed its more efficient performance than the existing blockchain consensus algorithm. The proposed algorithm has a fast computing transaction speed of about 3 s and reduces the memory usage by 38.5%. In addition, it provides a secure remote environment by solving security vulnerabilities in the IoT environment.